Pengaruh Penerapan Media Pembelajaran Flipbook Maker Terhadap Hasil Belajar Siswa pada Mata Pelajaran Dasar-Dasar Desain Grafis di SMK Negeri 1 Luragung - Firmansyah, Muhamad Fahmi; Zakaria, Yoyo (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study was motivated by the lack of Flipbook Maker-based learning media in Computer Graphics classes at vocational schools, resulting in conventional learning processes that are less appealing to students. This study aims to develop and determine the effectiveness of Flipbook Maker-based learning media in improving student learning outcomes. The research method used is quantitative with a pre-experimental design using the One Group Pretest-Posttest model. The research subjects were 30 students in class X DKV 1 at SMK Negeri 1 Luragung. Data were collected through learning outcome tests in the form of pre-tests and post-tests, as well as student response questionnaires to determine the practicality of the media. Data analysis was conducted by comparing the average pretest and posttest scores and calculating the increase in learning outcomes using gain scores. The results showed that the average pretest score of 63.67 increased to 79.17 on the posttest, with a difference of 15.5 points. This increase shows that the use of Flipbook Maker media is effective in improving student learning outcomes in Computer Graphics. In addition, student response to this media was very good, as it was considered interesting, easy to use, and helpful in understanding the material. Thus, Flipbook Maker-based learning media is suitable for use as an innovative alternative in technology-based learning in vocational schools